The Effect of Family Environment And Future Orientation Through Learning Motivation Towards the Interest in Continuing to the College of State Senior High Schools Students in Pemalang Regency - Nurhayati, Suci; Dian Wisika Prajanti, Sucihatiningsih; Rusdarti, Rusdarti (Journal of Economic Education, 2021)
The National Education System is defined as a conscious and planned effort to create an atmosphere of learning and the learning process so that students can actively develop their potential to have spiritual strength, self-control, personality, intelligence, morality, media as well as the necessary skills needed by them, society, nation and state. Education is expected to form the Indonesian people who are able to master science and technological development required to build Indonesia. The method used in this research using regression analysis techniques model path analysis. The population in this study was carried out on grade XI students of State Senior High school in Pemalang Regency. The sampling technique in this study using cluster sampling technique. The variables in this study are independent variables which include the family environment, future orientation, while the dependent variable is the interest in continuing to the college of state senior high schools students in Pemalang. Data collection techniques using questionnaires and documentation. The research results showed that the family environment had a positive and significant effect on learning motivation. Future orientation has a positive and significant effect on learning motivation. Family environment has a positive and significant effect on interest in continuing to college through learning motivation. Future orientation has a negative and insignificant effect on interest in continuing to college through learning motivation. Learning motivation has a positive and significant effect on the interest in continuing to college.